Експериментальна перевірка сформованості готовності майбутніх учителів математики до інноваційної педагогічної діяльності - Ачкан, Віталій (My University, 2018)
У статті охарактеризовано етапи та складові експериментальної перевірки авторської концепції формування готовності майбутніх учителів математики до інноваційної педагогічної діяльності, зокрема охарактеризовано критерії сформованості готовності майбутніх учителів математики до інноваційної педагогічної діяльності та наведено засоби діагности для кожного із критеріїв. The article describes the stages and individual components of the experimental verification of the author's concept of forming the readiness of future mathematics teachers for innovative pedagogical activity. In particular, the criteria and indicators of the readiness of future mathematics teachers for innovative pedagogical activity are characterized, diagnostic tools are provided for each of the criteria, on the example of the motivation-value component, the algorithm for calculating the coefficient is illustrated, which characterizes the level of formation of this component, the results of measuring the level of the formation of the motivational-value component of readiness for innovative pedagogical activity at the end of the pedagogical experiment are presented.
Keywords: готовність до інноваційної педагогічної діяльності; вчитель математики; засоби діагностики; readiness for innovative pedagogical activity; teacher of mathematics; diagnostic tools